CLIMATE S ROLE IN CHANGING THE FACE OF THE EARTH AND THE SPATIAL CONFLICT PROBLEMS: A PRELIMINARY STUDYON THE CIMANUK WATERSHED - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
The increasedglobal climate directly affects theface of the earth. In addition to result in shifting of season and extremeweather, the relatively rapid change in temperaturebeing climate element also gives impact on intensity of geomorphology process (weathering, erosion, sedimentation). This paper describes how the escalated climate affects the process 'of weathering and erosion as well as change in delta mainland size and its contribution to the emergence of spatial conflict. DAS Cimanukwas selected as the study case area. The escalated air temperature for a long period directly escalates the acceleration of rock weathering, which in turn accelerates the erosion of weathered rock due to rainfall to be sediment material through erosion process. During period of 1963 - 2002, Cimanuk delta area enlarged more than 350.000 m2/year. This new land, which is formed by weathering and erosion processes in the Cimanuk River Basin through peels of land surfacepredicted to be averagely more then 10 em/year. In the last, the new landformed by geomorphologic processes triggering the new source of conflict potentially.